Species-level characterization of the core microbiome in healthy dogs using full-length 16S rRNA gene sequencing - Rojas, Connie A.; Park, Brian; Scarsella, Elisa; Jospin, Guillaume; Entrolezo, Zhandra; Jarett, Jessica K.; Martin, Alex; Ganz, Holly H. (Frontiers in Veterinary Science, 2024)
Despite considerable interest and research in the canine fecal microbiome, our understanding of its species-level composition remains incomplete, as the majority of studies have only provided genus-level resolution. Here, we used full-length 16S rRNA gene sequencing to characterize the fecal microbiomes of 286 presumed healthy dogs living in homes in North America who are devoid of clinical signs, physical conditions, medication use, and behavioral problems. We identified the bacterial species comprising the core microbiome and investigated whether a dog’s sex & neuter status, age, body weight, diet, and geographic region predicted microbiome variation. Our analysis revealed that 23 bacterial species comprised the core microbiome, among them Collinsella intestinalis, Megamonas funiformis, Peptacetobacter hiranonis, Prevotella copri, and Turicibacter sanguinis. The 23 taxa comprised 75% of the microbiome on average. Sterilized females, dogs of intermediate body sizes, and those exclusively fed kibble tended to harbor the most core taxa. Host diet category, geographic region, and body weight predicted microbiome beta-diversity, but the effect sizes were modest. Specifically, the fecal microbiomes of dogs fed kibble were enriched in several core taxa, including C. intestinalis, P. copri, and Holdemanella biformis, compared to those fed raw or cooked food. Conversely, dogs on a raw food diet exhibited higher abundances of Bacteroides vulgatus, Caballeronia sordicola, and Enterococcus faecium, among others. In summary, our study provides novel insights into the species-level composition and drivers of the fecal microbiome in healthy dogs living in homes; however, extrapolation of our findings to different dog populations will require further study.